Rat Island as a Natural Laboratory: Exploration of Environmental Physics Concepts - Maulana, Yudi; lestari, Endah; Fitriani, Detty; Dinata, Kristian; Tri W, Endah; Johan, Henny (Sainsmat : Jurnal Ilmiah Ilmu Pengetahuan Alam, 2024)
This research aims to reveal the potential of Rat Island as a marine ecotourism destination as well as a contextualized physics learning environment. Using the descriptive qualitative method and literature review support, data were obtained through field observations and literature analysis related to sediment topography, climate, and physics concepts such as ocean waves and tree height measurements. Previous research stated that Rat Island has marine ecotourism potential that can be used as contextual physics learning material. Observation activities in the natural laboratory of Rat Island by Master of Science Education students succeeded in increasing the enthusiasm for learning and inquiry skills. Physics analysis related to tree height measurement provides a deep understanding of physics concepts that can be applied in everyday life. In addition, the research showed the tidal pattern on Rat Island as a periodic physical phenomenon that can be studied and predicted. The concept of Rat Island as a natural laboratory supports its potential as a place for learning and experimentation while supporting environmental conservation efforts. Overall, Rat Island has great potential as a source of contextual physics learning and a sustainable marine ecotourism destination.Keywords: Rat Island, Physics Learning, Tidal Wave, Natural Laboratory.